Decision analysis
Decision Analysis is dedicated to advancing the theory, application, and teaching of all aspects of decision analysis. The primary focus of this journal is to develop and study operational decision-making methods. The journal bridges the gap between theory and practice thereby facilitating active communication and exchange of knowledge among decision analysts in academia, business, industry, and government.